PUBLIC DEBT ANALYSIS BASED ON SUSTAINABILITY INDICATORS - DASCALU, Elena (Annals of Spiru Haret University. Economic Series, 2016)
This article is an analysis of public debt, in terms of sustainability and vulnerability indicators, under a functioning market economy. The problems encountered regarding the high level of public debt or the potential risks of budgetary pressure converge to the idea that sustainability of public finances should be a major challenge for public policy. Thus, the policy adequate to address public finance sustainability must have as its starting point the overall strategy of the European Union, as well as the economic development of Member States, focusing on the most important performance components, namely, reducing public debt levels, increasing productivity and employment and, last but not the least, reforming social security systems. In order to achieve sustainable levels of public debt, the European Union Member States are required to establish and accomplish medium term strategic budgetary goals to ensure a downward trend in public debt.